Dynamics of identification and conflict: anthropological encounters - Abu-Manga, al-Amin; Benda-Beckmann, Keebet von; Bošković, Aleksandar; Eidson, John R.; Dereje Feyissa; Finke, Peter; Foblets, Marie-Claire; Gabbert, Echi Christina; Galaty, John G.; Höhne, Markus Virgil; Osman, Elhadi Ibrahim; Pelican, Michaela; et al. (Berghahn Books, 2023)
Dealing with the dynamics of identification and conflict, this book uses theoretical orientations ranging from political ecology to rational choice theory, interpretive approaches, Marxism and multiscalar analysis. Case studies set in Africa, Europe and Central Asia are grouped in three sections devoted to pastoralism, identity and migration. What connects all of these anthropological explorations is a close focus on processes of identification and conflict at the level of particular actors in relation to the behaviour of large aggregates of people and to systemic conditions
Keywords: Aufsatzsammlung